Monetary transfers from children and the labour supply of elderly parents: Evidence from Vietnam - Ha Trong Nguyen; Amy Y. C. Liu; Alison L. Booth (Institute for the Study of Labor (IZA), 2012)
In the absence of a broad-based pension scheme, the elderly in developing countries may rely on monetary transfers made by their children and on their own labour supply. This paper examines whether monetary transfers from children help to reduce elderly parents' need to work. Taking the possible endogeneity of children's transfers in the parents' labour supply into account and using maximum likelihood methods and Vietnamese data, we find that monetary transfers help the elderly cope with risks associated with old age or illness. At the same time, however, monetary transfers are not sufficient to fully substitute for parents' labour supply.
Keywords: J14; J22; J26; 330; old-age support; labour supply; inter-generational transfers; endogenous variable; maximum likelihood; Privater Transfer; Alterssicherung; Eltern; Arbeitsangebot; Vietnam